The Malaysian creative content industry: how do we fare vis a vis United States and South Korea? - Daud, Mahyuddin; Abdul Ghani Azmi, Ida Madieha; Ali, Adibah; Alavi, Rokiah; Ismail, Suzi Fadhilah (2018)
The Malaysian creative content industry is a young industry, having its origins as early as in the 1930s. It proves its potential where many emerging local talents are being recognized and accepted by the international audience. Unfortunately, it is not at par with other rapidly evolving content industries like the Korean hallyu culture or the United States’ Hollywood industry. Several factors have been cited for this, namely the conflicting interest between the original creators and the corporate or private investors in Malaysia especially with regards to residual payments which rarely exists in Malaysia. Poor quality scripts and constraints in terms of production performance due to the limitation of funding and budgets are among other identified factors. It is claimed that private investors tend to manipulate the business model to gain higher profit margin and this deprives the rights of the original creators. This is the core issue that the paper will explore by employing a qualitative method i.e. doctrinal analysis and semi structured interviews by studying existing model framework on content industry developed in the United States and South Korea in order to propose recommendations to improve the content creator's rights in Malaysia. Preliminary result of the study showed that in Malaysia, content creators could not survive only on the earnings from acting to sustain their life without resorting to other part time jobs, unlike the Hollywood industry. The paper will contribute in further enhancing the Malaysian creative content industry as it is one of the Entry Point Project in the Malaysian Economic Transformation Program.